2009
DOI: 10.1002/jobm.200800297
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of diisodecyl phthalate (DIDP) by Bacillus sp. SB‐007

Abstract: In this study, diisodecyl phthalate (DIDP) was efficiently degraded by Bacillus sp. SB-007. The optimal conditions for DIDP (100 mg l(-1)) degradation by Bacillus sp. SB-007 in a mineral salts medium were found to be pH 7.0 at 30 degrees C, stirring at 200 rpm. The specific rate of DIDP degradation was found to be concentration dependent with a maximum of 4.87 mg DIDP l(-1) h(-1). DIDP was transformed rapidly by Bacillus sp. SB-007 with the formation of monoisodecyl phthalate and phthalic acid, which subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…While butyl benzoate may come as a consequence of monobutyl phthalate decarboxylation (and it is unknown whether it is then further processed into benzoate as this intermediate was not detected), phthalic anhydride may function as a detoxification strategy during the build-up of phthalate. Phthalic anhydride was previously detected during the degradation of the long-chain PAEs DINP and DIDP, , as well as dipentyl phthalate . A dihydroxy acid dehydratase (3668) that could be responsible for catalyzing this reaction was slightly upregulated in both the presence of phthalate and DBP (i.e., 1.9-fold; Supporting Information Table S5); however, it is also possible that this could occur through a hydrolysis reaction for which a number of enzymes could be responsible or spontaneous decay of phthaloyl-CoA as suggested during anaerobic biodegradation of phthalate. , The hydrolyzed DBP side chains, that is, two butanol molecules, are further metabolized through the action of alcohol and aldehyde dehydrogenases (3195 and 5697, respectively) and a fatty acid-CoA ligase (1663) before entering the short-chain fatty acid β-oxidation pathway (4429–4434), a pathway previously suggested, and for which all enzymes were strongly upregulated in this treatment (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While butyl benzoate may come as a consequence of monobutyl phthalate decarboxylation (and it is unknown whether it is then further processed into benzoate as this intermediate was not detected), phthalic anhydride may function as a detoxification strategy during the build-up of phthalate. Phthalic anhydride was previously detected during the degradation of the long-chain PAEs DINP and DIDP, , as well as dipentyl phthalate . A dihydroxy acid dehydratase (3668) that could be responsible for catalyzing this reaction was slightly upregulated in both the presence of phthalate and DBP (i.e., 1.9-fold; Supporting Information Table S5); however, it is also possible that this could occur through a hydrolysis reaction for which a number of enzymes could be responsible or spontaneous decay of phthaloyl-CoA as suggested during anaerobic biodegradation of phthalate. , The hydrolyzed DBP side chains, that is, two butanol molecules, are further metabolized through the action of alcohol and aldehyde dehydrogenases (3195 and 5697, respectively) and a fatty acid-CoA ligase (1663) before entering the short-chain fatty acid β-oxidation pathway (4429–4434), a pathway previously suggested, and for which all enzymes were strongly upregulated in this treatment (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…41,73,74 Here, we show that phthalate is toxic to both organisms, even when an additional carbon source is present (Supporting Information Figure S4), but that there are a number of adaptations adopted by the two isolates to deal with phthalate toxicity, for example, via conversion into phthalic anhydride, as observed by metabolomics, or the production of stress response mechanisms and efflux pumps, as shown by proteomics. While phthalic anhydride was previously reported in other PAE biodegradation studies 29,30,61 and is known to be less toxic than phthalic acid, 75 the mechanisms or reasons for its production were not discussed in these studies. While it is possible that the dehydration of phthalate could occur spontaneously at high temperatures, many previous PAE degradation studies have not reported phthalic anhydride production.…”
Section: ■ Discussionmentioning
confidence: 97%
See 2 more Smart Citations